2022
DOI: 10.3390/biom12020223
|View full text |Cite
|
Sign up to set email alerts
|

A Stepwise Framework for the Systematic Development of Lipid Nanoparticles

Abstract: A properly designed nanosystem aims to deliver an optimized concentration of the active pharmaceutical ingredient (API) at the site of action, resulting in a therapeutic response with reduced adverse effects. Due to the vast availability of lipids and surfactants, producing stable lipid dispersions is a double-edged sword: on the one hand, the versatility of composition allows for a refined design and tuning of properties; on the other hand, the complexity of the materials and their physical interactions often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Given the vast array of lipids available to produce NLCs, the most promising core compositions were selected by the microscopical and macroscopical assessment of the physical compatibility between liquid and solid lipids, which was performed in a similar way to the lipid compatibility and miscibility procedures described by Basso et al [ 28 ]. Q solubilization within the most promising lipids or lipid mixture at different wt% was also microscopically and macroscopically evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Given the vast array of lipids available to produce NLCs, the most promising core compositions were selected by the microscopical and macroscopical assessment of the physical compatibility between liquid and solid lipids, which was performed in a similar way to the lipid compatibility and miscibility procedures described by Basso et al [ 28 ]. Q solubilization within the most promising lipids or lipid mixture at different wt% was also microscopically and macroscopically evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Surfactants act as a barrier between the lipid matrix on the outside of the particles. Solid lipids that can be used are saturated fats in the form of free fatty acids, mono- and diglycerides, triglycerides, and other fatty acid esters that act as binders of active substances or drugs in the lipid matrix [ 43 , 44 , 45 ].…”
Section: Development Of Lipid Nanoparticles Technology In the Form Of...mentioning
confidence: 99%
“…Many studies have reported variation in the entrapment efficiency of active ingredients in carriers using various lipids or oils. This is because drugs demonstrate a variable solubility in these lipids and oils [37,38].…”
Section: Drug Loading and Entrapment Efficiencymentioning
confidence: 99%